2015
DOI: 10.1038/ncomms7180
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative model for charge carrier transport, trapping and recombination in nanocrystal-based solar cells

Abstract: Improving devices incorporating solution-processed nanocrystal-based semiconductors requires a better understanding of charge transport in these complex, inorganic–organic materials. Here we perform a systematic study on PbS nanocrystal-based diodes using temperature-dependent current–voltage characterization and thermal admittance spectroscopy to develop a model for charge transport that is applicable to different nanocrystal-solids and device architectures. Our analysis confirms that charge transport occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
130
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(148 citation statements)
references
References 51 publications
17
130
1
Order By: Relevance
“…Indeed, such a process is an effective way to intentionally introduce sensitizing centers in order to promote gain in photoconductors, 23 though such centers are detrimental to realising high efficiency high speed photodiodes. Furthermore, the activation energy and the density of the traps are both NC size 45 and Si 92 devices enabling them to efficiently detect UV and near-IR light respectivelty. MEG has also been exploited in PbS photoconductor devices, enhancing the responsivity of the device in the UV regime with an internal gain >100% at 220 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such a process is an effective way to intentionally introduce sensitizing centers in order to promote gain in photoconductors, 23 though such centers are detrimental to realising high efficiency high speed photodiodes. Furthermore, the activation energy and the density of the traps are both NC size 45 and Si 92 devices enabling them to efficiently detect UV and near-IR light respectivelty. MEG has also been exploited in PbS photoconductor devices, enhancing the responsivity of the device in the UV regime with an internal gain >100% at 220 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The current focus of much research remains in deep understanding of trap associated charge transport behaviour in PbS NCs and their role in influencing the device performance. [30][31][32][33]45,46 As the gain is principally achieved via a prolonged carrier lifetime this limits the temporal response of the device that requires a fast recombination and subsequent collection of charge carriers. This sets up a fundamental trade-off between photoconductor gain and the bandwidth.…”
Section: Pbs Nanocrystal Photodetectorsmentioning
confidence: 99%
“…Jeong et al [17] applied dedicated ligand optimization to increase photocurrent in PbS NP based solar cells, suggesting that surface trap states limit the electrical transport in PbS NP films. A recent study by Bozyigit et al [18], identified trap states as the major limitation in dark electrical conduction in PbS NP films, and the results indicate that the traps may be related to variations in PbS NP stoichiometry. The observed discrepancy between dark conductivity and photoconductivity in PbS NP films was addressed in a theoretical study by Shabaev et al who argued that the physical mechanisms of electrical transport are fundamentally different in the dark and under illumination [19].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the series resistance is determined by the mobility (µ) of the NC-solid (R s ∝ µ), which is very sensitive to tunnel barrier height and width between NCs. 25,26 Our previous observations of substitution of S by I (Figure 1(b)) and the increase in the exciton energy (Figure 1(c) inset) indicate that the I 2 treatment forms a thin wider band gap PbI 2 shell on the NCs. This shell acts as a barrier for charge carriers and is consistent with the 5-fold reduction of the mobility.…”
mentioning
confidence: 99%
“…Since E µ is given by the optical exciton energy, 25 it increases by 20 meV (Figure 1(c) inset) between the REF device and the I 2 device. The second term (n id kT log(J sc )) in Eq.…”
mentioning
confidence: 99%